Calcium fluoride as an efficient mineralizer for low-temperature portland cement clinkering: a mechanistic mini review - Mend, Bilguun; Lee, Youngjun; Kwon, Do-Young; Kim, Jang-Ho Jay; Chu, Yong-Sik (Frontiers in Materials, 2026)
Reducing the clinkering temperature of Portland cement is a key strategy for lowering energy consumption and CO2 emissions. Among various mineralizers, calcium fluoride (CaF2) has been widely reported as an effective additive for promoting clinker formation at reduced temperatures. This mini review summarizes recent mechanistic insights into the role of CaF2 in facilitating low temperature alite (C3S) formation. Available evidence suggests that CaF2 exerts its mineralizing effect through interconnected mechanisms, including enhanced lattice defect formation, accelerated ionic diffusion, and early liquid-phase development. Fluoride ions (F−) are proposed to substitute for oxygen sites in the C3S structure, generating calcium vacancies that facilitate the C2S-to-C3S transformation at lower temperatures. At the melt scale, CaF2 reduces melting temperature and viscosity, thereby improving ionic transport and phase combination. CaF2 addition is also frequently associated with the preferential formation of high symmetry alite polymorphs under reduced thermal conditions. When combined with metal oxides such as TiO2, CuO, and ZnO, CaF2 often exhibits synergistic effects that further enhance clinker formation efficiency. In addition, waste-derived CaF2 has been shown to retain mineralizing activity comparable to natural fluorite, supporting resource efficiency and circular-economy approaches. Overall, CaF2 is a promising mineralizer for low-temperature, energy-efficient, and low-carbon cement manufacturing, while its effectiveness remains system-dependent.